Perceived authenticity, perceived novelty risk and experiential value perception to revisit heritage destination in Melaka and Penang / Zaharah Mohamed Rani - Mohamed Rani, Zaharah (Institute of Graduate Studies, UiTM, 2015)
For decades now, tourist revisit intention has been the subject of debate in the tourism discipline, and especially within marketing. Although the tourism industry is growing worldwide, the industry continues to experience unpredictability over revisit intentions. Heritage is one of the core tourism products which have the potential to appeal to tourists, since heritage attractions permit the tourist to explore and experience the priceless character of past and present. However, when compared to other tourism segments, studies of tourist revisit intention in the discipline of heritage tourism, and especially for the case of Malaysia, continue to be neglected. Thus, the present thesis serves as a bridge to fill the gap and remedy the inconsistent empirical findings, by investigating tourist perceptions in the context of heritage tourism. The theoretical framework of the present study includes three constructs of independent variables namely perceived authenticity (object-based and existential authenticity), perceived novelty risk, and experiential value perception (host-guest relationship and activity). Empirical assessment of the theoretical framework includes a survey of 510 tourists who visited heritage tourism destinations in Malaysia, specifically Melaka and Penang. The resulting data were analysed through a process of multivariate analysis namely Structural Equations Modelling (SEM) using Analysis of Moment Structures (AMOS) software…